2013
DOI: 10.1681/asn.2013050458
|View full text |Cite
|
Sign up to set email alerts
|

Has the Yearly Increase in the Renal Replacement Therapy Population Ended?

Abstract: The recent decline in the number of new patients undergoing dialysis and transplantation in the United States may be linked to a reduction in the incidence of earlystart dialysis, defined as the initiation of renal replacement therapy (RRT) at an estimated GFR $10 ml/min per 1.73 m 2 . We examined the most recent data from the U.S. Renal Data System to determine how this trend will affect the future incidence of ESRD in the United States. The percentage of early dialysis starts grew from 19% to 54% of all new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…There is some evidence that the trend for initiation of dialysis at higher GFRs started to reverse in 2009 (13). This is also evident in Figure 2 in the article by Sood et al (8), in which there is a steady upward trend in early dialysis initiation until 2010.…”
mentioning
confidence: 80%
“…There is some evidence that the trend for initiation of dialysis at higher GFRs started to reverse in 2009 (13). This is also evident in Figure 2 in the article by Sood et al (8), in which there is a steady upward trend in early dialysis initiation until 2010.…”
mentioning
confidence: 80%
“…Despite recent evidence to the contrary (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), initial observational studies suggested that starting dialysis at higher levels of kidney function might be beneficial, and opinion-based clinical practice guidelines have generally supported a progressively more liberal approach to dialysis initiation (18). Until recently (19), there has been a pervasive temporal trend toward dialysis initiation at increasingly higher levels of eGFR (10,12,(20)(21)(22)(23). The drivers of this trend are poorly understood (6)(7)(8)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the trend toward a progressively earlier start of dialysis is not supported by clinical evidence (4,8). The early-start trend is related not just to patient comorbidity issues and renal function levels but also to provider biases and practice patterns.…”
Section: A Look Aheadmentioning
confidence: 83%